En quoi la diversité des stratégies pédagogiques participe-t-elle à la motivation à apprendre des étudiants ? Etude d’un cas particulier - Émilie Tremblay-Wragg; Carole Raby; Louise Ménard (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Many educational researchers support a variety of educational strategies to reap the benefits of each. Indeed, according to Sauvé, Debeurme, Wright, Fournier and Fontaine (2007), diversified pedagogical activities offer students the opportunity to make choices and break the routine while encouraging their motivation to learn. However, the motivation to learn from students who are subject to several educational strategies within the same course remains poorly documented. In response to this situation, this article describes the case of a university professor who uses several teaching strategies in his teaching. This case study was conducted through an interview with the professor, 12 hours of classroom observation and a questionnaire on motivation completed on three occasions during the session by his students as well as interviews with ten of them. The findings show that the methods employed by this professor, in addition to being diversified, are motivating for the students. Indeed, Carlos steps out of the traditional teaching framework by using 14 different teaching strategies as part of his course, thus providing a variety of learning opportunities that motivate his students. The article presents and discusses the factors contributing to this high level of student motivation by placing a strong emphasis on the instructional strategies.